Knowledge, Attitudes, Behavioural Practises, and Psychological Impact Relating to COVID-19 Among People Living With Spinal Cord Injury During In-Patient Rehabilitation in Bangladesh - Hossain, Mohammad Anwar; Hossain, K. M. Amran; Sakel, Mohamed; Kabir, Md. Feroz; Saunders, Karen; Faruqui, Rafey; Hossain, Mohammad Sohrab; Uddin, Zakir; Kader, Manzur; Walton, Lori Maria; Haque, Md. Obaidul; Shafin, Rubayet; et al. (Frontiers in Neurology, 2022)
Aim: The aim of this research is to focus on gaining an insight into the knowledge, attitudes, behavioral practices (KAP) and psychological impact relating to COVID-19 among the people living with spinal cord injury (SCI) receiving in-patient rehabilitation. Methods: A prospective, cross-sectional survey of people with SCI (N=207), who was inactive in-patient rehabilitation from two tertiary SCI Rehabilitation Centers in Bangladesh. Data was collected via face-to-face interviews, after voluntary consent, using a pretested, language validated questionnaire on KAP and the Depression, Anxiety, Stress Scale (DASS-21). Ethical approval and trial registration were obtained prospectively. Results: A total of 207 people with SCI responded. 87% were male and 13% female, with a mean age of 34.18±12.9 years. Within the sample group, people living with tetraplegia comprised 33.8% and people living with paraplegia comprised 66.2%. Overall, 63.8% of the participants were diagnosed with a SCI categorized as ASIA-A. Overall, the “knowledge score” was 8.59±2.3 out of 12; “depression”, 11.18±8; “anxiety”, 7.72±5.1; and “stress” was 9.32±6.7 from a total of 21 scores each category. The strong correlation was between knowledge, DASS scores and age (p<.05). In addition, there was a strong correlation between knowledge, gender (p<.05) and education (p<.01). Binary logistic regression found a stronger association of knowledge and DASS scores with gender, young age, illiteracy (p<.01), and rural residence (p<.05). Positive relationship was found between depression and anxiety scores (p<.01) and a moderate positive relationship was found between depression and stress scores (p<.01). A positive attitude was reported by the majority of participants (p<.05). In terms of behavioural practices, participants reported both self and caregiver had followed health advice with regard to consulting health professionals (65.7%), implementing isolation (63.8%), taking droplet precaution care (87.4%), and hygiene care (90.3%). Conclusion: Participants reported high levels of knowledge, adoption of positive attitude, and the practice of positive health advisory behaviors related to COVID-19 prevention procedures. However, high levels of depression, anxiety and stress were also reported. Overall, women and younger participants were more likely to have high KAP; whereas, those living in rural areas and with literacy challenges were less likely to report high knowledge scores.